2014
DOI: 10.2147/cia.s47367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive impairment in patients with Parkinson's disease: prevalence and risk factors

Abstract: BackgroundAlthough Parkinson’s disease (PD) is clinically characterized by motor symptoms, cognitive impairment is one of the most disabling non-motor symptoms. Despite it attracting increasing attention worldwide, less is known about its prevalence in the Chinese population. The objective of this study was to assess cognitive impairment and related risk factors in Chinese PD patients.MethodsWe collected the demographic, diagnostic, and treatment information of 901 PD patients from 42 centers throughout the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The global severity of PD, measured by HY stage, and motor symptoms in PD were strongly associated with the presence of any type of cognitive impairment. Previous studies and reviews have shown that motor impairment is related to the overall presence of cognitive impairment (70,71) and specifically to PD-MCI (72) and PDD (73,74). In line with these previous studies, we found that the presence of cognitive impairment was associated with a more severe HY stage of PD.…”
Section: Discussionsupporting
confidence: 91%
“…The global severity of PD, measured by HY stage, and motor symptoms in PD were strongly associated with the presence of any type of cognitive impairment. Previous studies and reviews have shown that motor impairment is related to the overall presence of cognitive impairment (70,71) and specifically to PD-MCI (72) and PDD (73,74). In line with these previous studies, we found that the presence of cognitive impairment was associated with a more severe HY stage of PD.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to age and educational level, other risk factors have been found for cognitive dysfunction in PD, including lower scores on performance tests, rigidity, postural instability, increased daytime sleepiness and white matter disease. 3 , 6 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, poorer cognitive performance and older age are associated with a higher risk of developing PD-MCI 36, 42, 47 . In particular, poorer performance on language, short-term recall and working memory tasks predicted future development of PD-MCI 47 .…”
Section: Epidemiology Of Pd-mcimentioning
confidence: 99%
“…Studies not using the IPMDS criteria have used various criteria to define PD-MCI (Table 1) and reported a lower, but still broad range, of prevalence estimates among newly diagnosed individuals: 9-24% 36-39 . Cross-sectional cohorts of patients with PD, enrolling patients with no restriction on disease duration, report a higher prevalence of PD-MCI, up to 55% 40-42, 44 . A large study incorporating data on 1346 patients without dementia of highly variable disease duration from 8 different centers found a prevalence of PD-MCI of 26% 45 .…”
Section: Epidemiology Of Pd-mcimentioning
confidence: 99%
See 1 more Smart Citation